Efektivitas Strategi Pembiasaan dalam Pembelajaran Akidah Akhlak untuk Peningkatan Akhlak dan Spiritual Peserta Didik (Penelitian di Pondok Pesantren Al Munawwar Ciawi Kabupaten Tasikmalaya) - Yanto Maulana Restu; Muhammad Rifa’i Arifin; Samsul Alam; Dede Sri Aliyya Nurussalam; Affandi Zamzam Fauzan (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This study is motivated by the increasing need to strengthen students’ moral character and spirituality through learning approaches that are not solely oriented toward cognitive aspects but also emphasize practical and sustainable implementation, particularly within the context of Islamic boarding school education. The objective of this research is to analyze the effectiveness of habituation strategies in Aqidah Akhlak learning in improving the moral and spiritual qualities of students at Pondok Pesantren Al-Munawwar Ciawi, Tasikmalaya Regency. This study employs a qualitative approach with a case study design, utilizing data collection techniques such as observation, in-depth interviews, and documentation. Data analysis is conducted using an interactive model consisting of data reduction, data display, and conclusion drawing in a systematic and continuous manner. The findings reveal that habituation strategies are implemented through structured religious routines such as Duha prayer, Qur’an recitation, and collective supplication, as well as the cultivation of moral values including honesty, discipline, politeness, and responsibility, supported by the active role of teachers as role models and mentors. The results indicate that habituation strategies effectively foster students’ discipline and responsibility, enhance respect toward teachers and peers, and encourage the consistent practice of Islamic behavior in daily life. In conclusion, habituation strategies have been proven to be an effective pedagogical approach for internalizing Aqidah Akhlak values and strengthening students’ spirituality in a holistic, integrative, and sustainable manner.   Keywords: Aqidah Akhlak, Students’ Spirituality, Habituation Strategy